Energy Consumption and Economic Growth in South Sudan - Ngor Timothy Ayong; Ernest Saina; Kipruto Kipruto (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2026)
This study analyzes the link between energy consumption and its impact on South Sudan's economic growth. The specific objective is to determine the impact of energy consumption on South Sudan's economic growth from 2010 to 2024. Endogenous growth theory was adopted as a grounding theory for the study, and the model was specified. An explanatory research design was employed to examine the short-run and long-run effects of energy consumption on economic growth in South Sudan. An ARDL model was used to check the effects of the dependent variables on the independent variable in the short run and long run. The ARDL bounds test produced an F-statistic of 1.985, which was less than the critical value for the upper bound I(1) at a 5% significance level (4.78), hence insignificant. The results show no cointegration between the variables; hence, there is no long-run relationship, confirming the existence of a short-run relationship. In contrast, in the short run, energy consumption shows a negative and insignificant relationship with GDP, attributed to oil fluctuations. In terms of policy, the South Sudanese government should encourage the use of renewable energy and adopt energy-saving measures, thereby reducing costs and increasing efficiency. Renewable energy and energy conservation policies should be adopted by the government to increase energy generation and support economic development, given that South Sudan is a growing nation.